PEMBUATAN BIODIESEL MINYAK JELANTAH MENGGUNAKAN BIOKATALIS EKSTRAK KASAR LIPASE DARI BIJI KESAMBI (Schleichera oleosa L.) - M A Nenobahan; M E. S Ledo; M Nitsae (Saintek Lahan Kering, 2020)
Biodiesel is one type of alternative diesel fuel that is environmentally friendly,can be updated and used as a substitute for diesel. Used cooking oil has the potential as a raw material for making biodiesel because it contains triglycerides and free fatty acis that can be converted into methyl esters. The general production of biodiesel is produced through esterification and transesterification reactions using chemical and biological catalysts. The purpose of this study was to determine the process of making biodiesel using used cooking oil with biocatalyst crude extract of kesambi seed lipase. The stages of research are, purification of used cooking oil, isolation of crude extract of lipase enzyme, analysis of hydrolysis activity test of transesterification activity, hydrolysis of oil esterification activity test, esterification activity, hydrolysis of oil esterification activity test, esterification reaction, separation of biodiesel, and characterization of biodiesel. The data analysis used was descriptive quantitative data analysis and the transesterification activity test was carried out by multiple linear regression test. Based on the results of the study it was obtained that the density was 0.8605 g/cm2, the viscosity was 1.397 mm2/s and the acid number was 0.65 mgKOH/g.Thus, making used cooking oil biodiesel using a crude lipase extract biocatalyst needs to be done in an effort to develop biodiesel production by utilizing kesambi seeds as biocatalysts.